2021
DOI: 10.3390/ani11123342
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Composition and Quality of Meat of Pulawska and Pulawska x PLW Crossbred Pigs Fed Rations with Naked Oats

Abstract: The study aimed to determine the impact of a 60% inclusion of naked oats in feed rations for Pulawska pigs and Pulawska x Polish Large White (PLW) crossbreds on the fattening performance, carcass composition, and meat quality. It was demonstrated that—independent from their diet—Pulawska pigs showed a daily weight gain about 14.5% lower (p ≤ 0.05), with about 15% higher feed conversion rate. The experimental factors showed no impact on the dressing percentage, meatiness, and backfat thickness, except that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It has been confirmed in research that the content of saturated, mono-and polyunsaturated acids in LTL and LL muscles of both Zlotnicka and Pw pigs depends on the composition of the genotype, feed and breeding method [9,11,25,28,41,43]. Migdał et al [25] and Cebulska et al [9] indicate statistically significant differences in the content of: palmitic, oleic, linoleic (LA), α -linolenic (ALA), gamma-linolenic (GLA), arachidonic (AA) and eicosatrienoic acid (DGLA) (Table 3).…”
Section: Fatty Acid Profilementioning
confidence: 81%
“…It has been confirmed in research that the content of saturated, mono-and polyunsaturated acids in LTL and LL muscles of both Zlotnicka and Pw pigs depends on the composition of the genotype, feed and breeding method [9,11,25,28,41,43]. Migdał et al [25] and Cebulska et al [9] indicate statistically significant differences in the content of: palmitic, oleic, linoleic (LA), α -linolenic (ALA), gamma-linolenic (GLA), arachidonic (AA) and eicosatrienoic acid (DGLA) (Table 3).…”
Section: Fatty Acid Profilementioning
confidence: 81%
“…Results obtained by most researchers indicate that the mean water content in the Pulawska breed is around 72-73% (Florowski et al, a, 2007Babicz et al, 2009;Milczarek and Osek, 2016;Milczarek et al, 2019). A slightly higher value -74.24%, was reported by Milczarek (2021). In turn, investigations by Debrecéni et al (2018) showed a slightly lower water content (69.8%) in meat from pigs of that breed.…”
Section: Muscle Composition Water Contentmentioning
confidence: 95%
“…In Table 2, slaughter and fattening traits in fatteners of Polish native pig breeds were shown. Among Polish local breeds Pulawska fatteners exhibit the highest daily body weight gains ranging from 780 g to 692 g (Tyra and Żak, 2010;Milczarek, 2021). Nevertheless, they are lower than those recorded for the Polish Large White and Polish Landrace pigsthe two most popular meat breeds kept in Poland (POLSUS, 2011;2023).…”
Section: Daily Weight Gainsmentioning
confidence: 97%
See 1 more Smart Citation